Analisis Kemampuan Berpikir Kritis Peserta Didik Kelas XI pada Materi Lingkaran - Firda Aisa Miftahunida; Rasiman Rasiman; Agus Setiawan (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
Critical thinking skills are abilities that must be developed and possessed by someone in an investigation that involves six indicators of Interpretation, Analysis, Evaluation, Inference, Explanation, and Self-Regulation. This study aims to describe students' critical thinking skills in solving math problems. The type of research used is descriptive qualitative where this method is used in analyzing students' critical thinking skills. The subjects in this study were SMA Negeri 2 Semarang class XI-9 students totaling 36 students, 26 female students and 10 male students, after consideration, the subjects were taken based on the level of ability in answering questions high, medium, and low. Techniques in data collection are observation, tests and interviews. Data validity uses triangulation techniques and the analysis techniques used in this study are data reduction, data presentation, and conclusion drawing. The results in this study that there are differences in students' critical thinking skills in solving mathematical problems where high level students are able to fulfill the indicators of six indicators optimally. Medium level students are able to fulfill four indicators less optimally. The low level is only able to achieve a few and not optimal.